Cardiac, skeletal, and ocular abnormalities in patients with Marfan's syndrome and in their relatives. Comparison with the cardiac abnormalities in patients with kyphoscoliosis. Issue 2 (February 1984) - Bruno, L; Tredici, S; Mangiavacchi, M; Colombo, V; Mazzotta, G F; Sirtori, C R
Abstract : Polygraphic (including apexcardiograms and carotid pulse tracings) and M mode echocardiographic examinations were carried out in 34 symptomatic patients with Marfan's syndrome; similar studies were performed in 32 relatives and in 34 young patients with kyphoscoliotic disease. The purpose of these investigations was to determine the association between cardiac and oculoskeletal abnormalities and to identify specific patterns of disease with a poor prognosis. Polygraphic tests showed significant changes in all patients with Marfan's syndrome: 74% showed the apical systolic click and murmur of mitral valve prolapse; 48% had the diastolic murmur of aortic regurgitation; isolated mitral valve prolapse was found in 52%, 26% had isolated aortic regurgitation, and 22% had a combination of the two. Echocardiographic changes were also found in all patients: 79% had aortic root dilatation; 48% fluttering of the anterior mitral leaflet; 79% mitral valve prolapse, mostly pansystolic; 34% both mitral prolapse and aortic root dilatation; and 34% left ventricular dilatation. The severities of the cardiac and oculoskeletal abnormalities were not correlated. The high prevalence of mitral valve prolapse found in these patients, which did not vary with age or sex, was also present in their relatives: mitral prolapse was present in 38% and aortic dilatation, with or without regurgitation, in 14%. Four of the relatives had clearcut Marfan's syndrome, and at least four others a forme fruste. The metacarpal index was abnormal in 41% of the relatives; ocular abnormalities were rare. In kyphoscoliotic patients only an increase in the prevalence of mitral prolapse (18.2% in women, none in men) was found. These findings underline a complex pattern of association between cardiac, ocular, and skeletal abnormalities in patients with Marfan's syndrome and confirm an appreciable inheritability of several of the markers of the disease.